2019
DOI: 10.1108/pr-06-2018-0197
|View full text |Cite
|
Sign up to set email alerts
|

In search of perfect boundaries? Entrepreneurs’ work-life balance

Abstract: Purpose Does the self-employed nature of entrepreneurs’ business ventures mean that they have perfect boundaries between their work and nonwork lives? Drawing on border theory, the purpose of this paper is to examine entrepreneurs’ work–life balance (WLB) in terms of how they construct and manage the borders between their work and nonwork lives. Design/methodology/approach The authors adopt a qualitative research approach to enhance their insight into entrepreneurs’ WLB using border theory. The study benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 66 publications
2
42
0
Order By: Relevance
“…By contrast, studies reveal that entrepreneurs find it difficult to separate the boundaries between work and family (Adisa et al , 2019b; Pareek and Bagrecha, 2017). This is due to the flexibility of being able to work everywhere that is associated with entrepreneurship, and entrepreneurs are accustomed to long working hours (Adisa et al , 2019b).…”
Section: Women and Work–family Balancementioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, studies reveal that entrepreneurs find it difficult to separate the boundaries between work and family (Adisa et al , 2019b; Pareek and Bagrecha, 2017). This is due to the flexibility of being able to work everywhere that is associated with entrepreneurship, and entrepreneurs are accustomed to long working hours (Adisa et al , 2019b).…”
Section: Women and Work–family Balancementioning
confidence: 99%
“…In addition, Johansson Sev€ a and € Oun (2015) advocate self-employment (based on the assumption that it facilitates flexibility) as a strategy for managing the competing demands of work and family. By contrast, studies reveal that entrepreneurs find it difficult to separate the boundaries between work and family (Adisa et al, 2019b;Pareek and Bagrecha, 2017). This is due to the flexibility of being able to work everywhere that is associated with entrepreneurship, and entrepreneurs are accustomed to long working hours (Adisa et al, 2019b).…”
Section: Women and Work-family Balancementioning
confidence: 99%
“…However, only a few studies have investigated the aspects of WLB among the self-employed. Adisa et al (2019) explored whether entrepreneurs' self-employed nature means that they possess perfect boundaries between work and non-work activities. The study found that self-employed entrepreneurs prioritise work over non-work activities and tend to have little consideration for limitations since they work from everywhere and for long hours.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the influence on family life, exists, and the hypothesis that entrepreneurship influence family life is accepted, as confirmed by previous researchers, (Gunnarsson et al,. 2017;Mordi 2019). Family life of people engaging in entrepreneurship venture, could face several challenges mainly due to the entrepreneurship demands for time and continues presence and concentration of the entrepreneur, as the sole responsible for the success or failure of the business.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%